Evolution of light-harvesting complex proteins from Chl c-containing algae - Hoffman, Gabriel (2011)
Light harvesting complex (LHC) proteins function in photosynthesis by binding chlorophyll (Chl) and carotenoid molecules that absorb light and transfer the energy to the reaction center Chl of the photosystem. Most research has focused on LHCs of plants and chlorophytes that bind Chl a and b and extensive work on these proteins has uncovered a diversity of biochemical functions, expression patterns and amino acid sequences. We focus here on a less-studied family of LHCs that typically bind Chl a and c and that are widely distributed in Chl c-containing and other algae. Previous phylogenetic analyses of these proteins suggested that individual algal lineages possess proteins from one or two subfamilies, and that most subfamilies are characteristic of a particular algal lineage, but genome-scale datasets had revealed that some species have multiple different forms of the gene. Such observations also suggested that there might have been an important influence of endosymbiosis in the evolution of LHCs.